ChemInform Abstract: Cu‐Catalyzed 1, 2‐Dihydroisoquinolines Synthesis from o‐Ethynyl Benzacetals and Sulfonyl Azides. Issue 14 (8th April 2014) - Sun, Lang; Zhu, Yuanxun; Lu, Ping; Wang, Yanguang
Abstract An efficient synthesis of 1, 3‐ and 1, 1‐dialkoxy‐1, 2‐dihydroisoquinolines from o‐ethynylbenzacetals and sulfonyl azides via a cascade process combining copper‐catalyzed alkyne—azide cycloaddition (CuAAC), Dimroth rearrangement, 1, 5‐OR shift/1, 5‐H shift, and 6π‐electrocyclic ring closure (6p‐ERC) is described.